Management of Patients of Recurrent Pterygium by Intralesional Injection of 5 Fluorouracil - Muhammad Amin, Iftikhar-Ul-Haq Tareen, Muhammad Afzal Khan, Saifullah Khan Tareen, Saira Bano, Chakar Tajwidi, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Management of recurrent pterygium using intralesional injection of 5-fluorouracil (5-FU) is an emerging technique aimed at reducing recurrence and inflammation without the need for repeated surgical intervention. Objective: To manage the patients of recurrent pterygium by intralesional injection of 5 fluorouracil. Methodology: This prospective study was conducted at Teaching Hospital, Loralai from 1st January 2023 to 30th June 2023 and 100 patients (100 eyes) including recurrent pterygium on clinical diagnosis were enrolled. The primary outcomes of the study were progression arrest, reduction of redness/lesion vascularity and secondary outcomes were cosmetic benefits, improvement of redness, irritability as well as astigmatism effects. A comprehensive eye examination was performed as baseline. Following the injections, visual acuity was evaluated, corneal topography was performed. All injections were administered in the outpatient clinic using a slit lamp. Ten minutes prior to the procedure, topical anesthesia (1% w/v tetracaine minims, Bausch & Lomb, UK) and 5% w/v povidone iodine eye drops (Bausch & Lomb, UK) were instilled. A pre-loaded 1 ml syringe containing 0.3 ml of 5FU (2.5 mg per 0.1 ml) was used to inject 0.1–0.2 ml (equivalent to 2.5–5 mg of 5FU) into the body of the pterygium using a 30-gauge needle. The formation of a bleb confirmed intra-lesional delivery of the drug. After the injections, 1–2 drops of 0.5% chloramphenicol were applied topically and continued four times daily for three days post-injection. All patients had 24-hour access to an emergency eye care service and could contact the investigators with any concerns during the study. Results: The mean age of the patients was 55.1±3.5 years with 60% males and 40% females. The progression arrest was noticed in 100% cases. However, 4 cases presented recurrence and later had to opt surgical interventions. The pterygium length was reduced in 60% cases with a mean difference of vector magnitude up to 0.10mm. Optical coherence tomography (OCT) measurements showed a reduction in pterygium thickness in 85% of patients, while the remaining patients exhibited no change. Among the patients who demonstrated a reduction in clinical grade, 90% showed an improvement of one grade, while 10% improved by two grades. The mean clinical grade decreased from 2.313 before the injection to 1.630 after the injection (P < 0.001; 95% CI: 0.368–1.007). The pterygium length was clinically graded as reduced in 65% cases while it remains in same grade in 35% ofcases. The photographic images of the patients showed reduction in the vascularity of the eye and redness with the injections. Conclusion: The application of intralesional 5 fluorouracil injections is significantly effective in recurrent cases, only 25% cases recurrence. Keywords: Management, Recurrent Pterygium, Intralesional injection, 5 Fluorouracil